A Prospective Clinical Study to EvaluAte the AbiliTy of the CloudCath System to Detect Peritonitis During In-Home Peritoneal Dialysis (CATCH) - Rajnish Mehrotra; Don E. Williamson; C. Ross Betts; Barbara A. Greco; Eric Yu; Aly El-Badry; Brian Fisher; Paul D. Mehoudar; Benjamin Briggs; Glenn M. Chertow (Kidney International Reports)
Introduction: Peritonitis is the leading complication of peritoneal dialysis (PD). Patients are instructed to seek care promptly for signs (cloudy effluent) or symptoms (abdominal pain), and earlier treatment improves outcomes. The CloudCath Peritoneal Dialysis Drain Set Monitoring (CloudCath) system monitors turbidity in dialysis effluent and sends notifications of changes signaling possible peritonitis. Methods: We conducted this single-arm, open-label, multicenter study of CloudCath system use during PD. We deactivated system notifications to participants and investigators, who followed standard-of-care for peritonitis signs and symptoms. Effectiveness endpoints measured time between CloudCath system notifications and peritonitis events using International Society of Peritoneal Dialysis (ISPD) criteria. Results: Two hundred forty-three participants used the CloudCath system for 178.8 patient-years. Of 71 potential peritonitis events, 51 events (0.29 per patient-year) met ISPD white blood cell (WBC) count criteria. The system triggered notifications for 41 of 51 events (80.4%), with a median lead time of 2.6 days (10%–90% range, –1.0 to 15.7; P < 0.0001). Excluding 6 peritonitis events that occurred when the system was not in use, the system triggered notifications for 41 of 45 events (91.1%), with a median lead time of 3.0 days (10%–90% range, –0.5 to 18.8; P < 0.0001). Of the 0.78 notifications per patient-year, the majority were peritonitis events or nonperitonitis events such as exit site and tunnel infections or catheter/cycler issues. Conclusion: The CloudCath system detected peritonitis events during PD several days earlier than the current standard-of-care and has the capacity to send notifications that could expedite peritonitis diagnosis and treatment.